The hCMEC/D3 cell line as a model of the human blood brain barrier - Weksler, Babette (BioMed Central, 2013)
Since the first attempts in the 1970s to isolate cerebral microvessel endothelial cells (CECs) in order to model the blood–brain barrier (BBB) in vitro, the need for a human BBB model that closely mimics the in vivo phenotype and is reproducible and easy to grow, has been widely recognized by cerebrovascular researchers in both academia and industry. While primary human CECs would ideally be the model of choice, the paucity of available fresh human cerebral tissue makes wide-scale studies impractical. The brain microvascular endothelial cell line hCMEC/D3 represents one such model of the human BBB that can be easily grown and is amenable to cellular and molecular studies on pathological and drug transport mechanisms with relevance to the central nervous system (CNS). Indeed, since the development of this cell line in 2005 over 100 studies on different aspects of cerebral endothelial biology and pharmacology have been published. Here we review the suitability of this cell line as a human BBB model for pathogenic and drug transport studies and we critically consider its advantages and limitations.